Efektivitas Model Pembelajaran Teams Games Tournament (TGT) Terhadap Kemampuan Membaca Permulaan Peserta Didik Kelas II di MI Ma’arif Wotbuwono Klirong - Anggraeni, Feni; Trisnawati, Oky Ristya (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The problem in this study is the low reading ability of grade II students at MI Ma'arif Wotbuwono Klirong due to the use of an ineffective learning model. The purpose of this study is to determine the effectiveness of the Teams Games Tournament (TGT) learning model on the initial reading ability of grade II students at MI Ma'arif Wotbuwono Klirong. This study uses a quantitative approach by applying a quasi-experimental design. The research population includes all grade II students at MI Ma'arif Wotbuwono Klirong which totals 54 students. In this study, the sampling technique was carried out by the nonprobability sampling method through saturated sampling or total sampling. The research sample consisted of 54 students in class II, with 28 students from class II A and 26 students from class II B. The research instrument is in the form of an initial reading ability test, which consists of a pretest and a posttest. Data analysis was carried out using descriptive statistical techniques as well as validity, reliability, normality, homogeneity, and t-tests. The results of the study show that the Teams Games Tournament (TGT) learning model is effective in improving the initial reading ability of grade II students at MI Ma'arif Wotbuwono Klirong. A significant increase can be seen from the average pretest score of 62.30 to 74.42 in the posttest. The results of the hypothesis test showed a sig value (2-tailed) of 0.014 which was smaller than 0.05, indicating a significant difference between the experimental class and the control class. Thus, the TGT model not only improves initial reading skills but also increases students' motivation and involvement in the learning process.